Ultrafast two-dimensional infrared spectroscopy for molecular structures and dynamics with expanding wavelength range and increasing sensitivities: from experimental and computational perspectives. Issue 3 (3rd July 2017) - Wang, Jianping
Abstract: Over the last decade, ultrafast two-dimensional infrared (2D IR) spectroscopy has been greatly advanced in a variety of aspects and is becoming a more exciting vibrational tool for understanding the structures and dynamics of condensed-phase equilibrium and non-equilibrium molecular systems, as well as surface-immobilised monolayers or adsorbates. A number of novel multi-pulse experimental schemes have been reported, some of them allow one to simultaneously examine anharmonic vibrational interactions and frequency–frequency correlations among vibrational chromophores having very different vibrational frequencies, particularly in a broadband fashion, providing potentially intrinsic spectroscopic probes for local, regional, and global molecular structures and dynamics; and some of them allow one to access more vibrational levels of a given set of anharmonic oscillators, enabling a better characterisation of their anharmonic potentials and factors influencing them. In this review, we first introduce these basic experimental schemes, mainly focusing on the time-domain methods. We then introduce technological and experimental advances on 2D IR signal detections that can provide much higher spectral resolution and higher sensitivities. Together, these advances can further increase the capacities of these nonlinear infrared methods. Computational considerations and developments on assessing more anharmonic potential parameters and simulating correlated broadband 2D IR spectra are then followed. Examples of the applications of these experimental and theoretical methods are also provided and discussed. We finally conclude this review by summarising these recent developments of the 2D IR methodologies and by discussing more advanced multi-pulse nonlinear IR experiments and their potential applications in near future.